O HUMOR NA INTERNET: REPRODUÇÃO OU PROBLEMATIZAÇÃO? - Ottoni, Maria Aparecida Resende (Intercâmbio, 2010)
In this article, we analyze a humoristic discursive genre: the joke, according to Critical Discourse Analysis (Fairclough, 2001a and b; Chouliaraki e Fairclough, 1999; Wodak & Meyer, 2001). We investigate how the identities are constructed in the joke, and if the discriminations and stereotypes are reproduced or questioned in it.